Analysis of Deformation Impact of Newly Constructed City Railway Subgrade on Adjacent Existing High-speed Railway Subgrade in Deep Soft Soil Areas - LI Zhenhua; WANG Changdan (Chengshi guidao jiaotong yanjiu)
[Objective] To effectively evaluate the impact of newly constructed city railway subgrade on the service performance of existing railway subgrade in deep soft soil areas, it is essential to study the vertical deformation of the new subgrade during construction and the horizontal displacement pattern of the adjacent existing high-speed railway subgrade. [Method] By combining field monitoring with numerical calculation methods, the vertical deformation of the newly constructed city railway subgrade at different filling stages and its influence on the horizontal displacement of the adjacent existing high-speed railway subgrade are analyzed. [Result & Conclusion] During the filling process of the newly constructed city railway subgrade, the vertical deformation undergoes four distinct phases: the gentle stage, the gradual accumulation stage, the significant deformation stage, and the stabilization stage. In the initial filling phase, the subgrade settlement is relatively small; as the load gradually increases, the settlement of foundation soil accelerates, eventually tending to stabilize. The horizontal displacement of the adjacent strata increases progressively with the increase in filling height, and the load effect becomes more pronounced as the filling height rises. The filling of the newly constructed suburban railway subgrade has certain impact on the settlement and horizontal displacement of the adjacent strata, but the impact is relatively minor compared to the settlement of the new constructed subgrade itself. The numerical simulation results are highly consistent with the field monitoring results, confirming the accuracy of the numerical model.